THE EFFECT OF ORGANIZATIONAL RESTRUCTURING AND REMUNERATION ON THE EFFECTIVENESS OF THE IMPLEMENTATION OF MAIN DUTIES AND FUNCTIONS OF THE CLERK'S OFFICE AND SECRETARIAT OF THE PONTIANAK HIGH COURT - Samza Januardi; Erdi Erdi; Darmanto Darmanto (DIA: Jurnal Administrasi Publik, 2023)
The purpose of this study is to explain the effect of organizational restructuring and remuneration on the effectiveness of the implementation of the primary duties and functions of the clerkship and secretariat of the Pontianak High Court. This study can be classified as survey research based on the research design. Meanwhile, in terms of the explanatory level, this study is associative. The object of this study is the organization of the clerkship and secretariat of the Pontianak High Court. The population in this study was employees within the Pontianak High Court, which amounted to 65 people. The study concluded that implementing organizational restructuring and remuneration greatly affects the effectiveness of implementing the main duties and functions of the clerkship and secretariat of the Pontianak High Court, both singly and jointly.